2019
DOI: 10.3389/fnmol.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

An IQSEC2 Mutation Associated With Intellectual Disability and Autism Results in Decreased Surface AMPA Receptors

Abstract: We have recently described an A350V mutation in IQSEC2 associated with intellectual disability, autism and epilepsy. We sought to understand the molecular pathophysiology of this mutation with the goal of developing targets for drug intervention. We demonstrate here that the A350V mutation results in interference with the binding of apocalmodulin to the IQ domain of IQSEC2. We further demonstrate that this mutation results in constitutive activation of the guanine nucleotide exchange factor (GEF) activity of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 51 publications
(89 reference statements)
3
53
2
Order By: Relevance
“…The four families showed moderate to severe ID in affected males, seizures, autistic traits and psychiatric problems were also reported in an inconsistent manner. To date, more than 70 mutations have been reported in IQSEC2 leading to moderate to severe intellectual disability with variable seizures and autistic traits . Although this gene has been included in Figure as possibly responsible for syndromic forms according to Neri et al, this review has failed in finding syndromic forms.…”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
See 1 more Smart Citation
“…The four families showed moderate to severe ID in affected males, seizures, autistic traits and psychiatric problems were also reported in an inconsistent manner. To date, more than 70 mutations have been reported in IQSEC2 leading to moderate to severe intellectual disability with variable seizures and autistic traits . Although this gene has been included in Figure as possibly responsible for syndromic forms according to Neri et al, this review has failed in finding syndromic forms.…”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
“…IQSEC2 has been shown to bind calmodulin in a calcium dependent manner through the IQ domain. Rogers et al showed that missense mutations on the IQ domain lead to impaired calmodulin binding, increase IQSEC2 GEF activity and lead to decreased AMPA receptor in brains of mice. These mice show abnormal behavioral phenotypes with increased locomotion, abnormal social interactions and decreased learning.…”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
“…Mutations in IQSEC2 were first described in families with non-syndromic XLID [43] and affected males showed moderate to severe intellectual disability, seizures, autistic traits, and behavioral disturbances as our patients do. To date, more than 70 mutations have been reported in IQSEC2 leading to a similar phenotype [44,45]. Some of these mutations are clustered in functional domains like IQ and Sec7 domains, which have been demonstrated to impair GEF activity [44,46,47].…”
Section: Family Id1208mentioning
confidence: 99%
“…However, as it is a missense variant and no other pathogenic missense variants have been reported at the CC domain, functional studies would be needed to establish its pathogenicity and understand its disease mechanism. phenotype [44,45]. Some of these mutations are clustered in functional domains like IQ and Sec7 domains, which have been demonstrated to impair GEF activity [44,46,47].…”
Section: Family Id1208mentioning
confidence: 99%
See 1 more Smart Citation